Between the political and politics: Infrastructure as hegemony in Israel and Palestine - Nolte, Amina; Justus Liebig University Giessen (My University, 2026)
This cumulative dissertation examines infrastructure as a hegemonic socio-material formation through the case of Israel and Palestine, with a particular focus on Jerusalem and its urban transportation systems. Bringing together perspectives from infrastructure studies, post-foundational political theory, and critical security studies, the dissertation develops the concept of “infrastructure as hegemony” in order to analyze how infrastructures materialize political orders spatially and temporally while simultaneously remaining sites of contestation and negotiation. The dissertation argues that infrastructures are not merely technical systems enabling circulation, mobility, and everyday life, but political projects that embody and stabilize specific relations of power. Drawing on the work of Antonio Gramsci, Ernesto Laclau, Chantal Mouffe, and Henri Lefebvre, the study conceptualizes infrastructures as sedimented political formations that shape social realities while appearing naturalized and apolitical in everyday life. At the same time, infrastructures remain open-ended assemblages through which political struggles, resistance, and alternative futures emerge. Empirically, the dissertation analyzes infrastructures of transportation, security, and urban governance in Jerusalem and beyond. Central case studies include the Jerusalem Light Rail, critical infrastructure and securitization practices, and “Safe” and “Smart City” projects. Through ethnographic fieldwork, discourse analysis, and critical spatial analysis, the dissertation demonstrates how infrastructures participate in processes of territorialization, selective inclusion and exclusion, securitization, and the production of political subjectivities. Particular attention is given to how infrastructures in contested urban environments mediate between state power, everyday life, and competing claims to space, mobility, and belonging. The dissertation further contributes to infrastructure studies by bridging debates between approaches that understand infrastructures as inherently political projects and approaches inspired by Science and Technology Studies (STS) and Actor-Network Theory (ANT), which emphasize relationality and socio-technical assemblages. By combining post-foundational theories of hegemony with methodological attentiveness to infrastructural practices and materialities, the study proposes an integrative framework for analyzing infrastructures as both politically grounded and continuously assembled through everyday practices. Overall, the dissertation highlights the ambivalent character of infrastructures: while they stabilize hegemonic orders and organize circulation, mobility, and security, they also create possibilities for disruption, resistance, and political transformation. In doing so, the study contributes to contemporary debates in sociology, political geography, urban studies, and critical security studies by demonstrating how infrastructures function as central sites through which political power, social order, and conflict are materially produced and contested.
Keywords: infrastructure; hegemony; security; Palestine; Israel; Jerusalem; ddc:300